A Feasibility Study on the Establishment of Wooden Chair Fun-Iture in 49 Susano Road, Corner Austria St. Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Wooden chair fun-iture is committed to provide personalized wood chair furniture to give and support what the customers’ needs and wants are through what design and style they wanted to be. It is important to have a chair not only for your own good, but in order to feel your visitors comfortable and relaxed. The business specializes in making a chair that essential for home like living area, dining area, offices, garden and etc. The Researchers conducted a Qualitative tool method such as interview and oral histories or life stories about the respondent experiences. The respondents have a freedom to speak about their ideas and suggestions for improving the business. The other tools were used by the researcher is Quantitative tool like Survey Questionnaire, it has a closed ended questions in order to know what are the respondent’s most wanted kind of chair and how it helps on their daily lives, it also asks the same question too large number of participants that measure opinions as numerical data.The survey results, analyze the visibility of the store that has a potential to meet the target market of the business, it is approachable and accessible for the future customers. The survey has 100respondents and 89 of this wants a personalize chair than the normal or simple chair, and Up to 80% above respondents afford the product offered. The technical viability, which all government ordinances can be easily obtained and the Financial viability analysis has a potential to gain profit through a year and eventually expand the company within a 5 years. The Wooden Chair fun-iture is a start-up business that offers personalize product that has a good quality and unique designs in order to satisfy the future client. This business is built to fulfill the passion on wood furniture. It also gives some freebies to make customers' satisfaction. This business has a garden theme design that the future, customers will feel the presence of garden in the store or showroom. The Wooden Chair fun-iture assures the professional work and quality of the product, it focuses on quality materials and having a skilled craftsmanship so that the product is definitely reliable and durable to satisfy the customers and in order to get the loyalties of the target market.
Keywords: wooden, furniture